2007
DOI: 10.1364/josaa.24.003827
|View full text |Cite
|
Sign up to set email alerts
|

Open-loop control of a MEMS deformable mirror for large-amplitude wavefront control

Abstract: A method is introduced for predicting control voltages that will generate a prescribed surface shape on a MEMS deformable mirror. The algorithm is based upon an analytical elastic model of the mirror membrane and an empirical electromechanical model of its actuators. It is computationally simple and inherently fast. Shapes at the limit of achievable mirror spatial frequencies with up to 1.5 microm amplitudes have been achieved with less than 15 nm rms error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 20 publications
0
60
0
Order By: Relevance
“…We recently implemented a computationally simple and inherently fast open loop control algorithm on a BU 140 actuator DM. Shapes at the limit of achievable mirror spatial frequencies were achieved with less than 15nm RMS error [11]. Others have also implemented open loop AO control with BU/BMC mirrors, demonstrating comparable results [12,13].…”
Section: Wavefront Correction Technologymentioning
confidence: 92%
“…We recently implemented a computationally simple and inherently fast open loop control algorithm on a BU 140 actuator DM. Shapes at the limit of achievable mirror spatial frequencies were achieved with less than 15nm RMS error [11]. Others have also implemented open loop AO control with BU/BMC mirrors, demonstrating comparable results [12,13].…”
Section: Wavefront Correction Technologymentioning
confidence: 92%
“…For input pre-shaping, an accurate dynamic model of the system is of paramount importance, if any performance improvement is expected. An open-loop method that predicted control voltages generating prescribed surface shapes on a MEMS deformable mirror was given in [110]. In this work, an analytic elastic model was used for the mirror membrane and an empirical electromechanical model was used for the actuator dynamics.…”
Section: B Open-loop Control With Input Pre-shapingmentioning
confidence: 99%
“…At least three different efforts have worked towards detailed modeling of the face sheet motion and how to control that surface with high precision. [15][16][17][18][19] However, our own work has shown that the non-linearity due to the face sheet is low enough that GPI does not require an advanced algorithm to determine actuator voltages. 20 Calibration of the quadratic voltage-phase relationship (see below) and the influence function are all that is necessary.…”
Section: Influence Function Superpositionmentioning
confidence: 99%